Emotional Intelligence and Clergy Work-Related Psychological Health among Anglican Clergy in England and Wales - Randall, Kelvin J. (Research in the social scientific study of religion, 2015)
The association between emotional intelligence and work-related psychological health is explored among a sample of 156 Anglican clergy in England and Wales who completed the Assessing Emotions Scale alongside the Francis Burnout Inventory. The data revealed that there was a negative correlation between emotional exhaustion and satisfaction in ministry; that higher levels of emotional intelligence were associated with higher levels of satisfaction in ministry; and that higher levels of emotional intelligence were associated with lower levels of emotional exhaustion.